2010
DOI: 10.1097/nmd.0b013e3181ea4e43
|View full text |Cite
|
Sign up to set email alerts
|

IQ Subtypes in Schizophrenia

Abstract: Intellectual decline, a key component of cognitive impairment in schizophrenia, varies considerably across individuals. To examine such cognitive heterogeneity, we applied cluster analysis of IQ and oral reading scores in 73 patients with schizophrenia. The following 3 empirically-derived subtypes emerged: intellectually compromised (42%) with similarly subaverage IQ (M = 79.90) and oral reading (M = 84.03); intellectually deteriorated (29%) with subaverage IQ (M = 86.81) but average oral reading (M = 107.71);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…While mixed reports have been published regarding the clinical significance of cognitive subgroups (Dawes et al, 2011;Geisler et al, 2015), the severely impaired subgroup in this instance was detected to exhibit greater negative symptomology compared to the moderate impairment and relatively intact subgroups. This is in line with several studies which suggest that individuals with SSD classified as having compromised cognitive capacity also experience more severe negative symptomology (Cobia et al, 2011;Potter & Nestor, 2010;Van Rheenen et al, 2018;Weinberg et al, 2016). However, as with previous research subgroups did not significantly differ in positive or affective symptom severity, suggesting that the cognitive subgroups identified in the current study do not reflect distinct clinical profiles, rather distinct executive phenotypes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While mixed reports have been published regarding the clinical significance of cognitive subgroups (Dawes et al, 2011;Geisler et al, 2015), the severely impaired subgroup in this instance was detected to exhibit greater negative symptomology compared to the moderate impairment and relatively intact subgroups. This is in line with several studies which suggest that individuals with SSD classified as having compromised cognitive capacity also experience more severe negative symptomology (Cobia et al, 2011;Potter & Nestor, 2010;Van Rheenen et al, 2018;Weinberg et al, 2016). However, as with previous research subgroups did not significantly differ in positive or affective symptom severity, suggesting that the cognitive subgroups identified in the current study do not reflect distinct clinical profiles, rather distinct executive phenotypes.…”
Section: Discussionsupporting
confidence: 92%
“…To date, investigations using cluster analytical techniques to characterise the cognitive heterogeneity within the schizophrenia spectrum have typically employed multidimensional batteries of cognition, with some studies entering indices of EF into the subgrouping analysis among other non-executive measures (Cobia et al, 2011;Dawes et al, 2011;Hill et al, 2002;Liu et al, 2011;Sauvé et al, 2018;Van Rheenen et al, 2017). When emergent subgroups are compared on select EF indices, meaningful differences are reported for some (Cobia et al, 2011;Gilbert et al, 2014;Liu et al, 2011;Van Rheenen et al, 2017), however not all subgroup comparisons (McDermid Vaz & Heinrichs, 2006;Potter & Nestor, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The cluster analysis approach has been successfully utilized in adults (13 studies) to detect neurocognitively homogenous subgroups in psychiatric disorders. Studies have examined neurocognitive clusters within specific disorders (i.e., schizophrenia, bipolar disorder, and gambling disorder) [27][28][29][30][31] or more commonly, across psychiatric disorders, such as examining across affective disorders, 32 across psychotic disorders, [33][34][35] and across the affect-psychosis spectrum. [36][37][38][39] The majority of studies identified three to four neurocognitive clusters, including a neurocognitively intact cluster and a globally impaired cluster.…”
Section: Adultmentioning
confidence: 99%
“…Some degree of variability in the affected domain was noted across studies due to the range of assessed neurocognitive domains, although visual memory deficits, psychomotor speed deficits, and executive deficits were specifically identified. Importantly, these distinct subgroups were associated with critical clinical/functional variables, in that generally the more impaired clusters were associated to worse outcomes/variables, such as symptomology, 27,31,32,35,[40][41][42][43] psychiatric episodes, 30,34 and response to clinical treatment 28 as well as years of education, 32,34 age, 31,34 employment status, 30,31 community functioning, 33 and socioeconomic status. 32…”
Section: Adultmentioning
confidence: 99%
“…Weickert et al [142] found that 51% of 117 patients with schizophrenia and decline in intelligence quotient (IQ) also exhibited deficits of executive function, memory, and attention. Deficits of executive function and memory also were found in 71% of 73 individuals with schizophrenia that showed intellectually compromised or deteriorated [143]. …”
Section: Potassium Channels and Clinical Conditions Holding Cognitmentioning
confidence: 99%